Living from Music in Salvador : Professional Musicians and the Capital of Afro-Brazil - Packman, Jeff (Jeff Loren) 1964- (Book collections on Project MUSE., 2021)
"Ethnography on working musicians, musical production, and labor in Salvador de Bahia, Brazil. Explores the concept of musical labor in relation to conditions of race and class"--